THE ROLE OF HALAL CERTIFICATION ON PURCHASE INTENTION TOWARDS FOOD PRODUCTS FROM MENA COUNTRIES: A SEM STUDY - Firdaus Fanny Putera Perdana; Muhammad Tahir Jan; Remzi Altunişik; Irwandi Jaswir; Betania Kartika (Bank Indonesia, 2019)
Kullu Halal (all Halal) is a concept that is highly applied in the Middle Eastern and North African (MENA) region as the majority of the population is Muslim. Many products from non-Muslim countries are also exported to the MENA countries and some of them are exposed to animal-based ingredients. Halal certification studies in the MENA region are found to be quite minimal to non-existent. The paper is designated to analyze the effects of Halal certification towards the purchase intention of Muslim consumers on food products from Muslim majority countries in the MENA countries. Theory of Planned Behavior (TPB) was used as a platform to predict the consumers’ intention to purchase the Halal certified products. A self-administered questionnaire was selected as a method and the respondents are the Muslim consumers living in certain areas of Klang Valley, Malaysia. Five hundred questionnaires were distributed, and 417 questionnaires were considered usable. Structural Equation Modeling (SEM) was used as a method in this research. Attitude, Subjective Norm, and Perceived Behavioral Control showed a strong correlation with Purchase Intention and the results were statistically significant at p < 0.05. Algeria was found to be the least trustworthy country by the respondents, followed by Iran, Lebanon, Iraq, and Bahrain. The results indicate that the presence of Halal certification is important and will be profitable for the food industry players in the MENA region. Despite being Muslim majority countries, it is important to ensure the presence of Halal certification in the products from MENA countries, especially from those that received low scores in the country of origin study.